ANALISIS KEBUTUHAN LAHAN PARKIR PADA PASAR KAHAYAN KOTA PALANGKA RAYA (Analysis Of Parking Land Requirements In The Market Kahayan City Palangka Raya) - Muhing Muhing; Tahan Tarif (Fakultas Teknik Universitas Kristen Palangka Raya, 2021)
Parking is basically a way to arrange vehicles according to the available places or areas. At a time when people used vehicles in large numbers, parking spaces could be found in almost all public places such as malls, offices, open park areas, development centers, and so on. When we talk about public parking, the main problem that is often faced is the lack of area of the parking lot itself, from the available parking space for two-wheeled vehicles, or land for four-wheeled vehicles. This study aims to determine the characteristics of parking and the capacity of parking needs at Kahayan Market, Palangka Raya City. From the results of the study, it can be obtained an overview of parking and the capacity of parking needs in the area so that it can provide input as evaluation material in the future for the creation of a safe and well-organized parking area. Based on the analysis, the number of Parking Space Units (SRP) in the Kahayan market, Palangka Raya City for two-wheeled vehicles is 79 parking lots and for four-wheeled vehicles 16 parking lots. For twowheeled vehicle parking index, the highest value is 25.32% 100% (parking demand can still be fulfilled) and for four-wheeled vehicles the highest is 18.75% 100% (parking demand can still be fulfilled). The highest accumulation value for two-wheeled vehicles occurred on Sunday with a total of 20 units and for four-wheeled vehicles it occurred on Wednesday with a total of 3 units. Keywords: Parking Space, Parking Location, Parking Capacity, Number of Vehicles